TEACHER’S REFLECTION ON THE DECREASING PARTICIPATION WITHIN ONLINE CLASSES - Dwi Agustina (Universitas Bandar Lampung, 2022)
The use of online classes used during covid-19 pandemic as the replacement of offline classes has affected the way teachers and students view language learning. Online classes are expected to function similarly as offline classes. However, teachers and students may find unequal aspects between the two teaching practices which make them prefer offline classes to online classes. This paper reports the findings in the writer’s study in which she observed the students’ participation from time to time within a semester teaching. This study aimed at discovering the dynamics of the students’ participation levels within online classroom. Recording the communication activities in the online classes, the writer found that the students’ participation varied across the time. The participation level was high in the beginning of the semester but it decreased significantly after the mid-term test. Comparing the participation level before and after the mid test, the writer found that the participation decreased 44% after the mid test. The average number of students’ responses was around 205 in a session before the mid test and the number decreased into around 115 per session. The significant decrease of the students’ participation in the class called for a teaching reflection. The writer as the lecturer felt the need to evaluate and reflect on her own teaching practices to reveal the reasons behind the decrease of students’ participation in her online classes. The reflection was presented to portray some issues emerging within the implementation of online classes.